Variability of temperature dependences of the retention of strongly polar compounds under ZIC‐HILIC liquid chromatographic mechanism. Issue 1 (25th January 2019) - Tanase, Maria; Bacalum, Elena; David, Victor
Abstract: The retentions of 13 strongly polar compounds (aminocids; dipeptides, drugs, and other biologically active species) were studied for two SeQuant ZIC‐HILIC (Merck) stationary phases containing a zwitterionic sulfobetaine moiety covalently attached to porous silica (3.5 and 5 μm particle size). Methanol and acetonitrile were used as organic components in the mobile phase composition, whose aqueous phase consisted in buffers of various controled pH values based on acetate‐acetic acid. This study shows various dependences of the retention on the absolute column temperature, some being obeyed to van't Hoff dependence, while others not following this rule. The values of standard enthalpy for the transfer of the analyte from mobile phase to the stationary phase were calculated from linear van't Hoff plots, which were below 10 kJ/mol. From the polynomial regression applied to the experimental retention data that not obeyed to a linear fit, the value of absolute temperature was calculated that corresponds to a maximum retention for studied compounds.